Highland avenger eaudiobook - Howell, Hannah (Murray Family, 2014)
Once, Arianna Murray Lucette believed that she'd met the man she could always rely on. She was wrong. Now she is fleeing for her life, and when her enemies attack a ship bound for her only refuge, she believes that all hope is lost—until she awakens on Scotland's shore to a pair of the most entrancing blue eyes she has ever seen. When Sir Brian MacFingal first spots the sun-streaked beauty on the beach, he mistakes her for dead. Soon, however, he discovers a woman who is more full of life and vitality than he ever dreamed possible. But though he knows he is fit to defend her life—even at the risk of losing his own—can such a raw warrior as he ever be worthy of her love? Contains mature themes.